On the First Three Extremum Values of Variable Sum Exdeg Index of Trees - Shu-Bo Chen; Syed Sheraz Asghar; Muhammad Ahsan Binyamin; Zahid Iqbal; Tayyeb Mahmood; Adnan Aslam (Complexity)
For a graph G, its variable sum exdeg index is defined as SEIaG=∑xy∈EGadx+ady, where a is a real number other than 1 and dx is the degree of a vertex x. In this paper, we characterize all trees on n vertices with first three maximum and first three minimum values of the SEIa index. Also, we determine all the trees of order n with given diameter d and having first three largest values of the SEIa index.